Synthesis and characterization of high silica content silicoaluminophosphate SAPO-35 from non-aqueous medium - Venkatathri, N. (Catalysis Communications, 2006)
SAPO-35 with up to 15.6 Si atoms per unit cell have been synthesized, using hexamethyleneimine as template in ethylene glycol medium (molar ratio of silica in the reaction gets up to 2.5). Crystallinity and silicon incorporation was confirmed by XRD, XRF, TG/DTA, SEM, FT-IR and Al-27 and Si-29 MASNMR. These SAPO-35 materials with high Si concentration show higher activity for methanol to olefin reaction than samples prepared with up to 0.3 molar ratio of silica in the get. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ammonia adsorption; FT-IR; MASNMR; methanol to olefin; non-aqueous medium; SAPO-35; SEM; TG/DTA; XRD

Synthesis and characterization of TAPO-31 molecular sieves using tripropylamine template - Venkatathri, N.; Shetty, V. N. (Catalysis Communications, 2006)
TAPO-31 was synthesized hydrothermally using a novel template tri-n-propylamine for the first time. C and N analysis shows the butanol from titanium tetrabutoxide plays an important role in the synthesis. The incorporation of titanium into framework of phosphorous and both aluminiurn and phosphorous sites was suggested from elemental analysis. Isomorphous substitution of titanium (III) in AlPO framework was confirmed from ESR and (31)p MASNMR spectra. UV-Vis and XPS spectra revealed a partial oxidation of framework titanium (III) into titanium (IV) in the calcined TAPO-31 and thus the presence of redox centers in the products. The higher titanium content (Al/Ti = 10) TAPO-31 sample shows higher activity for phenol hydroxylation compared to lower titanium content (Al/Ti = 20) and Titanium impregnated AIPO(4)-31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ESR; FT-IR; MASNMR; SEM; TAPO-31; TG/DTA; tripropylamine; UV-Vis; XPS; XRD

Synthesis, characterization and catalytic properties of vanadium aluminophosphate molecular sieves VAPO-31 and VAPSO-Amr from non-aqueous media - Venkatathri, N. (Applied Catalysis A-General, 2006)
Vanadium samples containing aluminophosphate molecular sieve (VAPO-31) and amorphous vanadium silicoaluminophosphate (VAPSO-Amr) have been synthesized using hexamethyleneimine template from non-aqueous media for the first time. XRD and SEM analyses confirm the phase purity of the synthesized samples. FT-IR analysis suggests the incorporation of V4+ in the aluminophosphate framework. ESR, UV-vis spectroscopic, and XPS techniques and cyclicvoltametric studies confirm the incorporation of vanadium and reveal its presence in tetrahedral and square pyramidal environments in the as-synthesized samples. Cyclic voltammetry reveals the presence of two redox couples in VAPO-31. This catalyst is found to be a good oxidation catalyst. Although most of the properties of VAPO-31NA and VAPSO-Amr are similar, the latter can access more vanadium and V4+ ions. Compared to aqueous media samples, it can incorporate more vanadium especially V5+, ions and has been found to be better oxidation catalyst. The physicochemical properties also change with media. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ESR; FT-IR; MAS NMR; non-aqueous; SEM; TG/DTA; UV-Vis; VAPO-31; XPS; XRD

Synthesis and MASNMR characterization of VPI-5 molecular sieve - Venkatathri, N. (Asian Journal of Chemsitry, 2007)
The synthesized VPI-5 sample was characterized by XRD, SEM, FTIR, TG/DTA, Al-27, P-31 and 3Q MASNMR techniques, which shows that the sample was highly crystalline. Carbon and nitrogen analysis reveals that the sample contains no template molecules; however, TG/DTA analysis shows the presence of physisorbed template molecules. MASNMR results show the presence of two different types of aluminium and phosphorus, 3Q MASNMR shows the presence of two types of environmentally different tetrahedral aluminium, which are not observable by ordinary MASNMR along with known octahedral aluminium.
Keywords: 3Q-MASNMR; FTIR; MASNMR; SEM; synthesis; TG/DTA; VPI-5; XRD